Evidence for Cross-Species Transmission of Covert Mortality Nodavirus to New Host of Mugilogobius abei - Zhang, Qing Li; Liu, Shuang; Li, Jun; Xu, Ting Ting; Wang, Xiu Hua; Fu, Guang Ming; Li, Xiao Ping; Sang, Song Wen; Bian, Xiao Dong; Hao, Jing Wei (Frontiers in Microbiology, 2018)
Viral covert mortality disease (VCMD), caused by covert mortality nodavirus (CMNV), is a newly emerging disease affecting most cultured shrimp and other crustaceans, but not fish. However, we discovered for the first time that Mugilogobius abei, a common marine fish collecting from shrimp farming ponds and surrounding coastal waters in China, was tested to be CMNV positive based on reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay. Further investigation based on the quantitative RT-LAMP assay indicated that 39% individuals of sampled M. abei were CMNV positive. Sequencing and alignment of sequences revealed that the partial RNA-dependent RNA polymerase gene of CMNV isolated from M. abei shared 98% homology with that from the original CMNV isolates. Histopathological analysis showed that CMNV infection in M. abei could induce extensive skeletal muscle necrosis, nervous tissue vacuolation in retina of eye and cerebellum of brain. Positive signals were verified in skeletal muscle, eye, brain and intestine by in situ hybridization (ISH) with CMNV probes. Under transmission electron microscope (TEM), CMNV particles were further visualized in the cytoplasm of neurogliocytes, granulocytes and myocytes in the CMNV positive samples diagnosed by ISH. All findings suggested that CMNV, a typical alphanodavirus originated from shrimp, could switch their hosts to fish by cross-species transmission. Meanwhile, the results reminded us to pay close attention to the high risk of CMNV to use fish as intermediate or new host as well as potentially spread or cause epidemic among cultured marine fish.